A Danish Blend: The Copenhagen Walkshop - Resmini, Andrea; Klyn, Dan; Lindenfalk, Bertil; Tedeschi, Miriam; Szuc, Daniel; Wong, Josephine (United States, 2025)
The walkshop introduces participants to an embodied, structural approach to understand, conceptualize, and design experiences that blend physical and digital space to create a novel space of action, with its own sense of presence, its own affordances, and its very special challenges. It consists of an outdoors morning walking and exploratory session, and of an afternoon mapping and reflective session at the conference venue. During the morning session, participants directly experience the urban fabric of Copenhagen and engage in activities meant to explore and expose the way digital and physical space commingle and become a layered blended space. During the afternoon session, the participants turn notes and observations into maps with the help of methods and tools provided by the facilitators. Attention is paid to identifying friction between pace layers and to the structure, participating elements, and relationships that support the experience in either digital, physical, or blended space, and to reflect on how the structures of embodiment and spatiality shape experience and act as important, non-interface level grounding elements in the design of human activity in all types of space. The walkshop concludes with a plenary discussion of the deliverables created by participants, what insights were gained in the process, and possible developments to follow.
DIS 2024 Proceedings of the 2024 ACM Designing Interactive Systems Conference